A virus-like particle vaccine candidate for influenza A virus based on multiple conserved antigens presented on hepatitis B tandem core particles. Issue 6 (1st February 2018) - Ramirez, Alejandro; Morris, Stephen; Maucourant, Sophie; D'Ascanio, Isabella; Crescente, Vincenzo; Lu, I-Na; Farinelle, Sophie; Muller, Claude P.; Whelan, Michael; Rosenberg, William
Highlights: Novel virus-like particle (VLP) used as a vaccine platform for influenza A virus. VLP contains conserved antigens from influenza HA and M2 in a single product. Serum from immunised mice is cross-reactive to multiple HA subtypes of influenza A. Immunised mice are protected from live challenge with PR8 and pandemic H1N1 strains. Findings have implications for the design of the next generation of influenza vaccines. Abstract: Existing Influenza A virus (IAV) vaccines target variable parts of the virus that may change between seasons. Vaccine design relies on predicting the predominant circulating influenza strains but when there is a mismatch between vaccine and circulating strains, efficacy is sub-optimal. Furthermore, current approaches provide limited protection against emerging influenza strains that may cause pandemics. One solution is to design vaccines that target conserved protein domains of influenza, which remain largely unchanged over time and are likely to be found in emergent variants. We present a virus-like particle (VLP), built using the hepatitis B virus tandem core platform, as an IAV vaccine candidate containing multiple conserved antigens. Hepatitis B core protein spontaneously assembles into a VLP that is immunogenic and confers immunogenicity to proteins incorporated into the major insertion region (MIR) of core monomers. However, insertion of antigen sequences may disrupt particle assembly preventing VLP formation or result in unstable particles. We have overcome these problems by genetically manipulating the hepatitis B core to express core monomers in tandem, ligated with a flexible linker, incorporating different antigens at each of the MIRs. Immunisation with this VLP, named Tandiflu1, containing 4 conserved antigens from matrix protein 2 ectodomain and hemagglutinin stalk, leads to production of cross-reactive and protective antibodies. The polyclonal antibodies induced by Tandiflu1 can bind IAV Group 1 hemagglutinin types H1, H5, H11, H9, H16 and a conserved epitope on matrix protein 2 expressed by most strains of IAV. Vaccination with Tandiflu1 results in 100% protection from a lethal influenza challenge with H1N1 IAV. Serum transfer from vaccinated animals is sufficient to confer protection from influenza-associated illness in naïve mice. These data suggest that a Tandem Core based IAV vaccine might provide broad protection against common and emergent H1 IAV strains responsible for seasonal and pandemic influenza in man.